2019
DOI: 10.1111/bjd.18265
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of topical treatments in atopic dermatitis: unexpectedly low use of emollients and strong correlation of topical corticosteroid use both with depression and concurrent asthma

Abstract: Summary Background Despite decades of use, the actual amounts of topical corticosteroids (TCS) and emollients used in moderate‐to‐severe atopic dermatitis (AD) under real‐world conditions are unknown. Thus, it remains unclear whether inadequate use is widespread. Objectives To quantify the use of TCS and emollients in moderate‐to‐severe AD. Methods Double‐blinded drug prescribing was recorded prospectively at the point of drug dispensing within a catchment area of approximately 450 000 people over a 31‐year pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Nonetheless, the availability of quantitative monthly data on TCS dispensed makes it likely that mean BSA involvement exceeded 10% at baseline across the cohort, as detailed previously. 11 This inference was further supported by measurement of EASI in an explorative patient group at baseline, which yielded a mean AE SD score of 22 AE 12 (n = 6). In addition, the presence of continued active AD in this patient cohort is further supported by the fact that significant time elapsed between primary care referral and (i) initial dermatology review (range 2-10 weeks), (ii) initiation of phototherapy (2-8 weeks) and (iii) completion of the first 10 courses of treatment (range 1-89 treatments per course).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Nonetheless, the availability of quantitative monthly data on TCS dispensed makes it likely that mean BSA involvement exceeded 10% at baseline across the cohort, as detailed previously. 11 This inference was further supported by measurement of EASI in an explorative patient group at baseline, which yielded a mean AE SD score of 22 AE 12 (n = 6). In addition, the presence of continued active AD in this patient cohort is further supported by the fact that significant time elapsed between primary care referral and (i) initial dermatology review (range 2-10 weeks), (ii) initiation of phototherapy (2-8 weeks) and (iii) completion of the first 10 courses of treatment (range 1-89 treatments per course).…”
Section: Resultsmentioning
confidence: 78%
“…Patient selection, assembly of cohort, data refinement and quality checks have been described in detail prevously. 11 Definition of observational window, cohort refinement and validation are detailed in Data S1. The overall design was a nonplacebo-controlled before-versus-after treatment analysis as detailed in Results below.…”
Section: Overall Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al . greatly extend our understanding of the atopic dermatitis adherence hurdle in a large, well‐designed, population‐based study of AD prescribing patterns . This observational cohort study included patients with moderate‐to‐severe AD seen by a dermatologist in Scotland's National Health Service from 1986 to 2017.…”
mentioning
confidence: 99%
“…However, Choi et al . have clearly demonstrated that steroid phobia is not the only (or perhaps the most important) hurdle to AD treatment success, with their critically important and novel finding that patients with AD are not using prescribed emollients either, with only about one‐third to one‐eighth of the recommended amount being used . The findings of Choi et al .…”
mentioning
confidence: 99%